Large-scale Wind-driven Structures in the Orion Nebula - C. R. O’Dell; N. P. Abel (The Astronomical Journal)
A study of [C ii ] 158 μ m and H i 21 cm spectroscopic images plus high-velocity-resolution optical and ultraviolet spectra has shown the structure of the Orion Nebula to be different from that found from the study of those data separately. The [C ii ] features recently identified as the [C ii ] shell are shown to be part of the Veil-B H i foreground layer. Jointly called the outer shell, it covers the bright Huygens Region and the Extended Orion Nebula. Its maximum expansion velocity is 15 km s ^−1 . Closer to θ ^1 Ori C there is a second expanding shell, called the inner shell. It has an expansion velocity of 27 km s ^−1 , and probably results from a more recent period of strong wind from one or more of the Trapezium stars. Even closer to θ ^1 Ori C there is a central high-ionization bubble, freely expanding toward the observer but slowed in the opposite direction by photoionized gas coming off the main ionization front. Utilization of spectroscopic measures of the equivalent width of H β shows that the enhanced emission in [C ii ] seen just outside the visual wavelength boundaries of the Orion Nebula is not caused by limb-brightening of the outer shell. This enhanced emission is due to the radiation field of the Trapezium stars being filtered by intervening residual neutral hydrogen. A velocity component near 30 km s ^−1 (heliocentric) first seen in H i is also present in [C ii ], and may result from a foreground cloud of the ISM.